Qualidade do serviço em organização do terceiro setor: um estudo na casa de apoio à criança com câncer - Campos, Rilson Flaubert de Paiva (2009)
The research aimed identify how the quality of services provided by Casa de Apoio à Criança com Câncer Durval Paiva is perceived by its users, giving an opportunity of improve their performance in social services provision pointing out the failures experienced, the institution will have the user as a important partner in fails identification, serving as a subsidy to the actions of correction and improvement to such situations demands. With this work implementation will be observed contributions that will permeate to the fields of theory and practice, enabling progress and enrichment on the subject. The theoretical contribution is observed as this work execution will provide greater advance about the models developed for the third sector. The proposed work will raise awareness issues about the full potential of the social economy, with regard to the quality of services provided by organizations, allowing a better definition of priorities on their development. The study addressed three issues: identifying the people that receive support of the Casa Durval Paiva, identifying what is the level of satisfaction of families served and evaluate the services provided by Casa Durval Paiva that demand improvements in the perception of families assisted. Found a demand for services has been found that the institution has a multidisciplinary team with a high level of professionalism, and supervised with students of various educational institutions and many volunteers to complement the actions of individual professionals. Was measured a high satisfaction of users of the services provided by Casa Durval Paiva